The recurrent homozygous translation start site variant in CCDC134 in an individual with severe osteogenesis imperfecta of non‐Morrocan ancestry. Issue 5 (12th January 2022) - Ali, Taccyanna M.; Linnenkamp, Bianca D. W.; Yamamoto, Guilherme L.; Honjo, Rachel S.; Cabral de Menezes Filho, Hamilton; Kim, Chong Ae; Bertola, Débora R.
Abstract: Osteogenesis imperfecta (OI) is a rare low‐bone mass skeletal Mendelian disorder characterized by bone fragility leading to bone fractures, with deformities and stunted growth in the more severe phenotypes. Other common, nonskeletal findings include blue sclerae and dentinogenesis imperfecta. It is caused mainly by quantitative or structural defects in type I collagen, although dysregulation of different signaling pathways that play a role in bone morphogenesis has been described to be associated with a small fraction of individuals with OI. Recently, a homozygous variant in the translation start site of CCDC134, showing increased activation of the RAS/MAPK signaling pathway, has been reported in three families of Moroccan origin with a severe, deforming form of OI. We report on a 9‐year‐old Brazilian boy, harboring the same homozygous variant in CCDC134, also presenting severe bone involvement. This report contributes to the phenotypic delineation of this novel autosomal recessive form of OI, which presents with high prevalence of nonunion fractures considered rare events in OI in general. In addition, it expands the phenotype to include base skull anomalies, potentially leading to serious complications, as seen in severe forms of OI. A poor response to bisphosphonate therapy was observed in these individuals. As the variant in CCDC134 leads to dysregulation of the RAS/MAPK signaling pathway, drugs targeted to this pathway could be an alternative to achieve a better management of these individuals.